The Impact of Covid-19 on The Execution of Audits in Malaysia - Muhammad Iqmal Hisham Kamaruddin; Mustafa Mohd Hanefah (Asian Journal of Accounting Perspectives, 2023)
Research aim: This study aims to investigate the impact of the Covid-19 pandemic on the execution of audits in Malaysia. This study also will examine the readiness of Malaysian auditors to work from home (WFH). Design/ Methodology/ Approach: A questionnaire survey was employed with 171 Malaysian external auditors participating. Research finding: This study found that all three audit areas – audit planning and fieldwork, group audit engagement and auditors’ reports – were highly impacted due to Covid-19. As for readiness to WFH, results show that Malaysian auditors are not ready to implement the approach. Conversely, Malaysian audit firms were ready to implement WFH. Theoretical contribution/ Originality: This study is among the few identifying the impact of Covid-19 on the execution of audits. It also contributes by identifying auditors’ and audit firms’ readiness to implement a WFH approach. Practitioner/ Policy implication: This study will benefit audit firms especially in implementing a WFH approach.